2004
DOI: 10.1002/jcb.20158
|View full text |Cite
|
Sign up to set email alerts
|

PTH and phospholipase A2 in the aging process of intestinal cells

Abstract: In this study we analyzed, for the first time, alterations in phospholipase A2 (PLA2) activity and response to parathyroid hormone (PTH) in rat enterocytes with aging. We found that PTH, rapidly stimulate arachidonic acid (AA) release in rat duodenal cells (+1- to 2-fold), an effect that is greatly potentiated by aging (+4-fold). We also found that hormone-induced AA release in young animals is Ca2+-dependent via cPLA2, while AA released by PTH in cells from aged rats is due to the activation of cPLA2 and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 77 publications
0
6
0
1
Order By: Relevance
“…The hormone increased the release of radioactive AA in pre-labeled intestinal cells via a Ca 2+dependent cPLA 2 activity (Gentili et al, 2004a). Recently, we showed, for the first time, alterations in PLA 2 activity and response to PTH in rat enterocytes with ageing (Gentili et al, 2004b). We found that PTH-dependent arachidonic acid release is greatly increased in cells from old rats.…”
Section: Pth Modulation Of Enterocyte Pla 2 Activitymentioning
confidence: 75%
See 1 more Smart Citation
“…The hormone increased the release of radioactive AA in pre-labeled intestinal cells via a Ca 2+dependent cPLA 2 activity (Gentili et al, 2004a). Recently, we showed, for the first time, alterations in PLA 2 activity and response to PTH in rat enterocytes with ageing (Gentili et al, 2004b). We found that PTH-dependent arachidonic acid release is greatly increased in cells from old rats.…”
Section: Pth Modulation Of Enterocyte Pla 2 Activitymentioning
confidence: 75%
“…In rat enterocytes, PKA activation is upstream of ERK1/2 activation (Gentili et al, 2001b), and the fact that PTH-induced phosphorylation of cPLA 2 is suppressed to a great extent by cAMP antagonists, suggest that the effect of PKA on cPLA2 is mediated through ERK1/2. Basal levels of cPLA 2 serinephosphorylation were higher in old enterocytes, affecting the hormone response, which was greatly diminished (Gentili et al, 2004b). cPLA 2 phosphorylation impairment in old animals was not related to changes cPLA 2 protein expression and did not explain the substantial increase on PTH-induced AA release with ageing, further suggesting the involvement of a different PLA 2 isoform.…”
Section: Pth Modulation Of Enterocyte Pla 2 Activitymentioning
confidence: 82%
“…The expression levels of lipogenesis controlling enzymes such as ATP-citrate and acetyl-CoA carbolase, 56 as well as cytosolic phospholipase A2 and phospholipase C-y1, 57 , 58 are reduced with age. On the contrary, overexpression of genes responsible for β-oxidation of fatty acids leads to life extension in Drosophila melanogaster 59 …”
Section: Genetics Of Aging and Longevitymentioning
confidence: 99%
“…При старении снижается экспрессия ферментов ли-погенеза АТФ-цитрат лиазы и ацетил-КоА карбоксилазы (Nogalska et al, 2003), а также цитозольной фосфоли-пазы A2 и фосфолипазы C-γ1 (Utsuyama et al, 1997;Gentili et al, 2004). Напротив, сверхэкспрессия генов β-окисления жирных кислот приводит к продлению жизни Drosophila melanogaster (Lee et al, 2012).…”
Section: генетика и эпигенетика старения и долголетияunclassified